Links between mothers’ ACEs, their psychopathology and parenting, and their children’s behavior problems–A mediation model - Hanetz-Gamliel, Keren; Dollberg, Daphna G. (Frontiers in Psychiatry, 2022)
Children of mothers with a history of adverse childhoods are at greater risk of behavior problems. However, the mechanisms through which a mother’s early adverse experiences (ACEs) are transmitted to her children need further study. Our goal was to examine a conceptual mediational model linking mothers’ ACEs, maternal psychopathology symptoms, and parenting behaviors with children’s internalizing and externalizing behaviors sequentially. A sample of 153 Israeli mothers of children ages 3-12 (52% girls) participated in the study, and most of the mothers (94.7%) were cohabiting with a spouse. Mothers completed online questionnaires about their early adverse experiences, psychopathology symptoms, parenting behavior, and their children’s internalizing and externalizing behavior. Results showed that mothers with higher ACE scores reported more maternal psychopathology symptoms and more internalizing behavior in their children. The mother’s psychopathology in and of itself mediated the link between her ACEs and her child’s internalizing and externalizing behavior. Moreover, an indirect sequential path emerged linking ACEs with the mother’s psychopathology symptoms, which, in return, were linked with hostile parenting. Hostile parenting, in turn, was linked with children’s internalizing and externalizing behavior. These findings highlight the complicated and intertwined ways in which adverse experiences early in the mother’s life might put her child’s wellbeing at risk. The findings suggest that ACEs are linked to maternal affect dysregulation, which interferes with parenting, increasing the risk of behavior problems in children. The findings underscore the need to assess mothers’ adverse history, psychological distress, and parenting behavior, and provide treatments that can reduce the intergenerational transmission of early adverse experiences.